Running a Reverse Osmosis Plant at Maximum Renewable Energy Use - Karimanzira, Divas; Rauschenbach, Thomas (European Journal of Applied Sciences, 2023)
Decentralized water and energy systems are increasingly seen as the most effective solutions for remote areas. This paper presents the development of a solar-powered reverse osmosis (RO) plant to provide water to a remote village. The objective is to optimize the use of renewable energy and maximize water production by implementing a control mechanism that can quickly adapt to changing operating conditions. To achieve this, the RO plant operates in batch mode and is controlled by a nonlinear model-based predictive controller. It also serves as an active load to effectively utilize solar energy. Fortunately, in arid and water-scarce regions, the water demand aligns well with solar power availability. Although a diesel generator is used as a backup, energy is stored as pressure in a pressure chamber and in batteries for direct electrical energy consumption by the plant. The energy-intensive tasks, such as driving the high-pressure pump and membrane cleaning, are scheduled during periods of abundant solar energy. Additionally, a module for predicting membrane fouling is developed to enable the controller to appropriately schedule membrane cleaning and pump operation, while considering the various limitations imposed by the RO plant components. The system has successfully met the water demand while maximizing solar power utilization.